2018 17th IEEE International Conference on Machine Learning and Applications (ICMLA) 2018
DOI: 10.1109/icmla.2018.00030
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Kernel PCA for Outlier Detection

Abstract: In this paper, we propose a new method to perform Sparse Kernel Principal Component Analysis (SKPCA) and also mathematically analyze the validity of SKPCA. We formulate SKPCA as a constrained optimization problem with elastic net regularization (Hastie et al.) in kernel feature space and solve it. We consider outlier detection (where KPCA is employed) as an application for SKPCA, using the RBF kernel. We test it on 5 real world datasets and show that by using just 4% (or even less) of the principal components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Figure 1 depicts how an exemplary yarn twist machine looks. In order to perform Sparse Kernel Principal Component Analysis (SKPCA) for outlier detection, Das et al [5] proposed a novel method. On five real-world datasets, they examined them, and they found that by employing just 4% of the main components (PCs).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 depicts how an exemplary yarn twist machine looks. In order to perform Sparse Kernel Principal Component Analysis (SKPCA) for outlier detection, Das et al [5] proposed a novel method. On five real-world datasets, they examined them, and they found that by employing just 4% of the main components (PCs).…”
Section: Introductionmentioning
confidence: 99%